URGENSI SUPERVISI AKADEMIK DALAM PENGEMBANGAN PROFESIONALISME GURU DI ERA INDUSTRI 4.0 - Moh Rofiki (Indonesian Journal of Basic Education, 2019)
This paper discusses the urgency of academic supervision in the development of teacher professionalism in the industrial era 4.0. Academic supervision is a series of activities in the form of providing professional services to help teachers develop their abilities (competencies) to better manage the learning process. In an era of disruption where all digital lines are added, plus access to information is very fast, the teacher as the central point of improving the quality of education as an impact on the quality of the learning process, the teacher's professionalism needs to continue to grow and develop so that the teacher can do his job professionally. Several ways can be used and implemented by the principal as a supervisor in carrying out academic supervision activities to improve teacher professionalism, namely: a. guidance for teachers, b. education and training, and c. increase teacher work motivation